PELATIHAN PERSIAPAN LAHAN TANAM DAN TEKNIK PEMASANGAN JARINGAN IRIGASI TETES PABRIKASI DI DESA SALUT KABUPATEN LOMBOK UTARA: land - Gede Jaya Negara, I Dewa; Spriyadi, Anid; Made Alit Karyawan, I Dewa; Bagus Budianto, Muh; Hari Kusumo, Bambang; Kisman, Kisman; Endang Susilawati, Lolita; Budi Santoso, Bambang; Priyono, Joko; Tajidan, Tajidan (Universitas Mataram, 2024)
In general, the potential for dry land in North Lombok Regency is very broad with low river water potential, including in Salut Village. This village is a fairly large area of ​​dry land and is a hilly area that has the potential to be used as agricultural land for horticultural crops. There is no surface water potential in this area and the only existing water source is groundwater, namely from deep groundwater wells. So the existing land has the potential to be used for farming seasonal crops such as chilies, tomatoes and others. However, because of the people's habit of carrying out agricultural activities in the rainy season, the land in the dry season is left idle. To increase land use in the dry season, it is necessary to encourage the creation of horticultural planting land so that in the dry season people can cultivate these crops. The aim of this service is knowledge and improving residents' skills in creating horticultural agricultural land for farming in the dry season using drip irrigation. This service stage consists of field inspection and outreach, land preparation practices and planting areas, preparation and installation of drip irrigation, discussions and questions and answers as well as evaluation. Finally, the community service has succeeded in training 7 community representatives in creating horticultural planting areas, such as clearing land, plowing, making plots and making beds. Participants were able to make planting beds because the plots of planting land were smaller and knew how to make and install drip irrigation in raised beds, and knew how to obtain and maintain it. The activity evaluation was carried out by the service team, when they saw the results of the land preparation during the implementation process by looking at their seriousness, the participants understood and gained additional knowledge in preparing planting land and installing drip irrigation networks on the land.